Управління інтелектуальними ризиками в проектах транспортування великогабаритних вантажів за допомогою теорії ігор - Становська, Іраїда Іванівна; Кошулян, Сергій Вікторович; Торопенко, Олексій Вікторович; Дадерко, Олеся Ігорівна (НТУ "ХПІ", 2018)
Показано, що транспортування великогабаритних вантажів є проектом, в якому команда останнього постійно стикається із інтелектуальними ризиками протидії оточуючого середовища у вигляді субпідрядників (шляховиків, електриків, автоінспекції, тощо) виконанню окремих етапів проекту. Управління цими ризиками містить різні форми співпраці із субпідрядниками, – від об’єднання (SCRUM-технології) до конкурентної гри із "супротивником". Запропоновано адаптивну комплексну структуру технології проектної діяльності з перевезення великогабаритного багажу, яка передбачає на початку кожного етапу виявлення форми співпраці із субпідрядником та гнучку технологію роботи із ним.

It has been shown that the transport of large-sized cargoes is a project in which the latter team constantly faces the intellectual risks of counteracting the environment in the form of subcontractors (roadmakers, electricians, road inspectors, etc.) for the implementation of individual stages of the project. Managing these risks involves various forms of cooperation with subcontractors, from the merger (SCRUM-technology) to the game with the "opponent". The adaptive complex structure of the project activity on transportation of large-sized luggage is offered, which provides at the beginning of each stage the identification of the form of cooperation with the subcontractor and the flexible technology of work with it. The aim of the work is to reduce the time and cost of implementing large baggage transportation projects by managing the intellectual risks of counteraction from subcontractors of the project through the development and implementation of an adaptive integrated structure of the project activity technology, which foresees, at the beginning of each phase of the project, the identification of the form of cooperation with the next subcontractors and the flexible working technology with them. To achieve this goal, the following tasks were set and solved: analyzed problems of transportation of large-sized cargoes and revealed design features of such activity; Estimated intellectual risks of counteraction to project activity from "subcontractors" of the project; proposed adaptive complex structure of technology project activity, which combines SCRUM technology and game; the industrial tests of the results of the research with a positive technical and economic effect have been carried out. The results of the work were used in the system of support for the adoption of design decisions in the context of intellectual risks "SOLINTR". The system "SOLINTR" was involved in the PEO "ECHO" when planning and equipping the project of transportation of large-sized cargo at a distance of 235 km with a positive technical and economic effect.
Intellectual risk management in projects of transportation of large vehicles by the game theory
Keywords: SCRUM-технології; конкурентна гра; адаптивна комплексна структура; центральнє ядро; ЦЯ; large-sized cargoes; SCRUM-technology; competitive game